Antibiotic prescribing practice in residential aged care facilities ‐ health care providers' perspectives. Issue 2 (21st July 2014) - Lim, Ching Jou; Kwong, Megan W‐L; Stuart, Rhonda L; Buising, Kirsty L; Friedman, N Deborah; Bennett, Noleen J; Cheng, Allen C; Peleg, Anton Y; Marshall, Caroline; Kong, David C M
Abstract: Objective: To explore organisational workflow and workplace culture influencing antibiotic prescribing behaviour from the perspective of key health care providers working in residential aged care facilities (RACFs). Design, setting and participants: Qualitative approach using semistructured interviews, focus groups and onsite observation between 8 January 2013 and 2 July 2013. Nursing staff, general practitioners and pharmacists servicing residents at 12 high‐level care RACFs in Victoria were recruited. Main outcome measures: Emergent themes on antibiotic prescribing practices in RACFs. Results: Sixty‐one participants (40 nurses, 15 GPs and six pharmacists) participated. Factors influencing antibiotic prescribing practice have been divided into workflow‐related and culture‐related factors. Five major themes emerged among workflow‐related factors: logistical challenges with provision of medical care, pharmacy support, nurse‐driven infection management, institutional policies and guidelines, and external expertise and diagnostic facilities. Lack of onsite medical and pharmacy staff led to nursing staff adopting significant roles in infection management. However, numerous barriers hindered optimal antibiotic prescribing, especially inexperienced staff, lack of training of nurses in antibiotic use and lack of institutional infection management guidelines. With regard to culture‐related factors, pressure from family to prescribe and institutional use of advance care directives were identified as important influences on antibiotic prescribing practices. Conclusions: Workflow‐ and culture‐related barriers to optimal antibiotic prescribing were identified. This study has provided important insights to guide antimicrobial stewardship interventions in the RACF setting, particularly highlighting the role of nurses.